A structured literature review of interventions used in the management of nonalcoholic steatohepatitis (NASH). Issue 3 (27th May 2019) - Povsic, Manca; Oliver, Louisa; Jiandani, Neha Raju; Perry, Richard; Bottomley, Juliana
Abstract: Nonalcoholic steatohepatitis (NASH) is a chronic, progressive disease, that can advance to fibrosis, cirrhosis, and hepatocellular carcinoma. Despite being a leading cause of liver transplantation, there are no approved pharmacological treatments. Our aim was to identify literature on management options in NASH. Our structured review of interventions treating NASH patients from English language publications between 1 January 2007 and 25 September 2017 elicited 48 eligible references. Lifestyle management was identified as the mainstay of NASH therapy. Vitamin E and pioglitazone reported reductions in steatosis; however, although recommended for some, no therapies are indicated in NASH. Multiple investigational treatments reported efficacy in mild‐to‐moderate fibrosis in Phase II/III NASH trials. Lifestyle management, although the focus of clinical guidelines, is insufficient for patients progressing to advanced fibrosis. With no clear guidelines for patients requiring interventions beyond lifestyle modification, long‐term outcomes data are needed, particularly in patients with moderate‐to‐severe fibrosis.